The Impact of Social Media on the Behavior and Social Interactions of Agrarian Religious Communities: A Five-Decade Bibliometric Analysis (1974–2024) - Abdul Riski (Kalijaga Journal of Communication, 2026)
This research provides a comprehensive bibliometric analysis to map the intellectual structure and evolutionary trends of studies concerning social media's impact on the behavior and social interaction within religious agrarian communities over a five-decade period (1974-2024). The study analyzes 656 documents retrieved from the Scopus database, employing Biblioshiny to elucidate publication dynamics, pivotal contributors, influential sources, and thematic transitions. Key findings indicate a marked exponential increase in annual publications, with PLoS One identified as the most prolific journal. Analysis of keywords reveals a predominant focus on concepts such as human, female, and religion. The mapping of international collaboration networks shows leadership by the United States, followed by Australia as the second most collaborative nation. Thematic evolution analysis demonstrates a significant progression from initial broad discussions to more nuanced explorations within specific religious contexts, including Islam, Christianity, and Hinduism, and their intricate connections to socio-economic development effects, rural planning, and cultural transformation. The study concludes that this field is both dynamic and expansive, characterized by growing scholarly interest. It highlights substantial avenues for future research, particularly in empirically investigating the nuanced role of social media in shaping the socio-cultural fabric, religious practices, and developmental trajectories of specific agrarian-religious communities, thereby addressing existing knowledge gaps.